Determinants of Related Party Transactions in Jordan: Financial and Governance Factors - Modar Abdullatif; Mohammad Alhadab; Israa Mansour (Australasian Accounting, Business and Finance Journal, 2019)
This study aims to explore the financial and governance factors that determine related party transactions (RPTs) in the developing country context of Jordan. To do so, a multiple regression model was developed and used. Results show that RPTs are negatively related with CEO-duality and board independence, while they are positively related with firm leverage, ownership concentration, board size, and audit quality. However, no statistically significant relation was found between RPTs and firm profitability or board political connections. Several of these relations (or lack of relations) are contrary to the findings of extant studies from more-developed countries, and can arguably be attributed to the prevalence of the closely-held business model in Jordan, where, regardless of the firm's financial conditions, high ownership concentration and close relations among board and top executive management positions are common, and the demand for an audit service of high quality is limited. Practical implications of these findings include that regulatory authorities in Jordan should enhance regulations and corporate governance codes to protect small shareholders and other stakeholders and restrict the power of dominant shareholders that makes them able to engage in illegitimate RPTs. In doing so, it also has to improve its monitoring of companies more likely to engage in such RPTs.
Keywords: Related Party Transactions; Profitability; Leverage; Ownership Concentration; CEO-duality; Board Size; Board Independence; Political Connections; Audit quality.